Analisis Pengaruh Investasi Daerah, Retribusi Daerah, Dan Belanja Daerah Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Deli Serdang - BR Sijabat, Lastri Putri; Yamani, Raisa; Tanjung, Ahmad Albar; Sukardi, Sukardi (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine how the influence of regional investment, regional retribution, and regional expenditure on local revenue in Deli Serdang Regency. This study uses annual data for the period 1993-2022. The type of research used is quantitative research. The data used is secondary data. This research is a time series study with the error correction model (ECM) method conducted with Eviews 10. The results of this study indicate that in the long run the variables of regional investment and regional expenditure have a significant positive effect on local revenue in Deli Serdang district. Meanwhile, the variable of local retribution in the long run has a significant negative influence on local revenue in Deli Serdang Regency. Meanwhile, in the short term, the variables of regional investment, regional retribution, and regional expenditure have a significant positive effect on local revenue in Deli Serdang Regency. Keywords: Local Revenue, Local Investment, Local Retribution, and Local Expenditure.